Editorial: FGF21 as a therapeutic target for obesity and insulin resistance: from rodent models to humans - De Sousa-Coelho, Ana Luísa (2023)
Obesity is a global pandemic that requires the urgent development of therapies and prevention strategies. To define new pharmacologic therapies or nutritional approaches it is mandatory to find new targets. Fibroblast growth factor 21 (FGF21) is considered a potential target to treat obesity, due to its favorable metabolic activity, signalling pathways and regulatory mechanisms. It is well-documented that FGF21 is induced by a wide range of biological stress conditions and a key signal that communicates and coordinates the physiologic response to restore the metabolic homeostasis in different tissues (1). FGF21 is elevated in pathological conditions such as obesity, insulin resistance, or fatty liver disease where an impairment of its signalling has been described (2). On the other hand, FGF21 analogues tested in overweight/obese patients with type 2 diabetes or NAFLD/NASH can reduce dyslipidaemia and steatosis, but improvements in glycaemic control or body weight were not globally restored (3). This suggests that pharmacologic effects of FGF21 are different from its physiological effects. In this Research Topic “FGF21 as a therapeutic target for obesity and insulin resistance: from rodent models to humans”, we include publications related to new advances involving FGF21, its signalling pathway, and its potential as a target to treat obesity